2006
DOI: 10.4049/jimmunol.176.10.6333
|View full text |Cite
|
Sign up to set email alerts
|

T Cell Responses Are Better Correlates of Vaccine Protection in the Elderly

Abstract: It is commonly held that increased risk of influenza in the elderly is due to a decline in the Ab response to influenza vaccination. This study prospectively evaluated the relationship between the development of influenza illness, and serum Ab titers and ex vivo cellular immune responses to influenza vaccination in community dwelling older adults including those with congestive heart failure (CHF). Adults age 60 years and older (90 subjects), and 10 healthy young adult controls received the 2003-04 trivalent i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
458
3
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 502 publications
(476 citation statements)
references
References 31 publications
13
458
3
2
Order By: Relevance
“…However, the influence of the vaccine on the prevalence of flu-like episodes may be difficult to estimate because of the heterogeneous etiology of these episodes in our setting, with only a small percentage related to influenza virus, even in non-vaccinated populations, <5 % outside the peak season and <25 % at the peak season (Sistema de Vigilância Epidemiológica da Gripe 2012, Brazil). We also did not assess cell-mediated immune responses to the vaccine, which are also affected by aging (McElhaney et al 2006). Some of the subjects enrolled in this study participated in a parallel study of the effects of aging on T cells, and in fact, there were several aspects of the biology of these cells that were improved in the trained groups [Silva and de Araújo, manuscript in preparation]; however, the cell-mediated responses to influenza antigens were not examined.…”
Section: Discussionmentioning
confidence: 99%
“…However, the influence of the vaccine on the prevalence of flu-like episodes may be difficult to estimate because of the heterogeneous etiology of these episodes in our setting, with only a small percentage related to influenza virus, even in non-vaccinated populations, <5 % outside the peak season and <25 % at the peak season (Sistema de Vigilância Epidemiológica da Gripe 2012, Brazil). We also did not assess cell-mediated immune responses to the vaccine, which are also affected by aging (McElhaney et al 2006). Some of the subjects enrolled in this study participated in a parallel study of the effects of aging on T cells, and in fact, there were several aspects of the biology of these cells that were improved in the trained groups [Silva and de Araújo, manuscript in preparation]; however, the cell-mediated responses to influenza antigens were not examined.…”
Section: Discussionmentioning
confidence: 99%
“…Although functional antibody responses are an accepted correlate for vaccine induced protection for vaccine licensure purposes [26], there are increasing reports that T-cell responses are important [27] and may be better correlates of vaccine protection especially in the elderly [28]. Whole virus vaccine may induce a more efficient cellular response than split or sub-unit vaccines [29,30] and this may be critical in preventing severe disease and death if not critical for prevention of infection.…”
Section: Discussionmentioning
confidence: 99%
“…In SLE, antibody responses to influenza vaccination are diminished (6), but cell-mediated responses have not been assessed. The latter are relevant, because it has been shown that in certain groups, such as the elderly, cellmediated responses to influenza vaccination can be a marker of clinical protection, independent from antibody responses (7). The most frequently used vaccine formulations are split virus or subunit vaccines.…”
mentioning
confidence: 99%